Plea of Non-Acceptance in Litigation: Balancing the Protection of Rights and the Stability of Judicial Proceedings - Hetatache , amor (Journal of Legal Studies and Researches, 2024)
Algerian civil and administrative courts grapple with the concept of the "plea of non-acceptance," a defense mechanism shrouded in ambiguity. Extensive legal discussions haven't clarified its definition or legal effects, leading to procedural hurdles. This research delves into its nature, how it differs from other defenses, and the legal consequences of its application under Algerian civil and administrative procedure law.